Pengembangan Media Roulette Game pada Mata Pelajaran IPS Materi Jenis-jenis Usaha dan Kegiatan Ekonomi Masyarakat Siswa Kelas 5 MI Miftahul Jannah - Saleem, Nurdina; Hidayat, Nurdin; Kurniasih, Try Indiastuti (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2024)
The problems in this research are 1) students' understanding of social studies material is still low, 2) the learning resources used during learning are only based on teacher books and student books, 3) most students in the class still tend to be passive in learning social studies and 4) the use of learning media, especially social studies learning, is still not varied. Based on these problems, it is necessary to develop learning media to overcome these problems, namely by developing roulette game media. The aim of this research is to determine the level of feasibility, practicality and effectiveness of the roulette game media in social studies subjects regarding types of business and economic activities in society. This type of research is the development of ADDIE (Analysis, Design, Development, Implementation and Evaluation). The instruments used are expert validation sheets, questionnaire sheets and test sheets. The results of research conducted by researchers in developing roulette game media in social studies subjects regarding types of business and economic activities in society stated that (1) this roulette game media received an average score of 4.5 (very valid) from media experts and obtained an average score of 4.3 (very valid) from material experts, (2) this roulette game media has a level of practicality based on teacher responses by obtaining an average score of 4.4 (very practical) and student responses by obtaining an average score of 3.6 (practical) (3) this roulette game media has a level of effectiveness based on the evaluation results obtained by students by looking at the learning completeness achieved at 85.71%. Based on this explanation, it can be concluded that the development of roulette game media has very high feasibility, practicality and effectiveness in class 5 social studies learning on types of business and community economic activities.